2019
DOI: 10.1111/ane.13072
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve ultrasound measurement in multiple sclerosis

Abstract: We were really involved in the Candeliere Merlicco et al 1 article concerning the use of the transorbital ultrasonography for measuring optic nerve atrophy in multiple sclerosis.We would like to congratulate the authors for their interesting work, but we would like to comment the methods they used to measure the optic nerve (ON) diameter.The authors used the B scan technique, an examination broadly utilized to diagnose ocular diseases, 2-7 that unfortunately is not sensitive enough in measuring orbital structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Optic neuritis may cause increased or decreased ONSD in the acute and chronic phases. 16,26,27 This may be an early and late sign of optic neuritis. The hypothesis that optic nerve thickness and stiffness may differ in optic neuritis with MS patients is the study's main purpose.…”
Section: Resultsmentioning
confidence: 99%
“…Optic neuritis may cause increased or decreased ONSD in the acute and chronic phases. 16,26,27 This may be an early and late sign of optic neuritis. The hypothesis that optic nerve thickness and stiffness may differ in optic neuritis with MS patients is the study's main purpose.…”
Section: Resultsmentioning
confidence: 99%
“…Although ONSD is a non-invasive method of ICP monitoring which creates a possibility of a false measurement, in our study all ONSD measurements were taken by at least two trained specialists with experience of using this method in clinical practice. The technique of a B-scan two-dimensional ultrasonography used in our study could be seen as a limitation of our study, due to a so-called "blooming-effect" [16]. However, there is enough published evidence showing the efficacy of the B-scan and there are analyses of the improvement and the development of higher frequency probes allowing brightness mode (B-mode) scanning to replace A-mode sonography [45].…”
Section: Study Limitationsmentioning
confidence: 92%
“…There is an ongoing issue, however, regarding which ultrasonography mode is best for evaluating the ocular structures. This was discussed, for example, by De Bernardo et al who suggested using a one-dimensional amplitude-mode (A-scan) technique over a two-dimensional brightness-mode (B-scan) [16]. However, a two-dimensional B-mode is also an accepted technique verified in transorbital ultrasonography according to available systematic reviews and a meta-analysis [17,18].…”
Section: Methodsmentioning
confidence: 99%
“…This technique is free of the "blooming" effect to allow more precise optic nerve identification and evaluation through the visualization of easily discernible high reflective spikes from the interface between arachnoid and subarachnoidal fluid. 7,8 Another important advantage of this ultrasound technique is the ability to perform the "30 degrees" test, a very useful test to discriminate between an ONSD increase related to raised intracranial pressure and an ONSD increase due to a solid thickening of the optic nerve. 9,10 In conclusion, we would like to suggest the use of the standardized A-scan technique, instead of B-scan ultrasonography, to obtain a more complete, accurate, and reliable optic nerve evaluation.…”
mentioning
confidence: 99%